Effects of repeated exposure to different concentrations of sevoflurane on the neonatal mouse hippocampus - Azimaraghi,Omid (2019)
Abstract Background and objectives: Developing brain is more vulnerable to environmental risk than is the developed brain. We evaluated the effects of repeated exposure to different concentrations of sevoflurane on the neonatal mouse hippocampus using stereological methods. Methods: Eighteen neonatal male mice were randomly divided into three groups. Group A, inhaled sevoflurane at a concentration of 1.5%; Group B, inhaled sevoflurane at a concentration of 3%; and Group C (control group), inhaled only 100% oxygen. Treatments were applied for 30 min a day for 7 consecutive days. The hippocampal volume, dendrite length, number of neurons, and number of glial cells were evaluated in each group using stereological estimations. Results: We identified a ∼2% reduction in the volume of the hippocampus in Group A compared to Group C. Mean hippocampal volume was ∼11% smaller in Group B than it was in Group C. However, these differences in hippocampal volume between the groups were not statistically significant (p > 0.05 for all). As for the number of neurons, we found significantly fewer neurons in Group A (∼29% less) and Group B (∼43% less) than we did in Group C (p < 0.05 for both). The dendrite length was ∼8% shorter in Group A and ∼11% shorter in Group B than it was in Group C. Conclusions: Repeated exposure to sevoflurane, regardless of the concentration, reduced the volume of the neonatal mouse hippocampus, as well as the number of neurons and dendrite length.